Al-Ghazali’s Philosophical Theology: By Frank Griffel (New York: Oxford University Press, 2009. 408 pages) (American Journal of Islam and Society, 2010)
This work of historical theology is essential reading for those wanting tounderstand with new depth and clarity the life and teachings of al-Ghazali(d. 505/1111). It is sometimes maintained that he contributed significantly toMuslim scholars’ ending of scientific inquiry and the use of reason. Thisview has recently been promoted afresh by Robert Reilly’s The Closing ofthe Muslim Mind (Wilmington, DE: 2010). Griffel extensively discusses twofactors contributing to this general perception: al-Ghazali’s opposition to thephilosophers in Tahafut al-Falasifah (see M. Marmura, ed and tr. The Incoherenceof the Philosophers [Provo, UT: 1997]) and his endorsement of occasionalism,the idea that events do not occur because of their inherent properties, such as fire’s ability to burn cotton, but instead God creates each individualevent with no reference to causes and effects in the physical world.Thus there is, at least in theory, no predictable causality in the world. Thiswould seem to render scientific inquiry, which relies on predictable processes,theoretically impossible. Scholars have differed over whether al-Ghazali is indeed an occasionalist (Marmura) or in fact endorses causality inline with the philosopher Ibn Sina (Richard Frank).In contrast, Griffel sets out to demonstrate that al-Ghazali “is the firstMuslim theologian who actively promotes the naturalization of the philosophicaltradition into Islamic theology” (p. 7) and that his writings are ‘aparticular kind of Avicennism’ (p. 14). His central argument is that al-Ghazali remained uncommitted throughout his career as to whether Godbrings about events in this world through occasionalism or via secondarycausality. Griffel contends that his consistent position was to regard eachposition as possible, developing “something like a synthetic positionbetween these two poles” (p. 12). In arguing for this, the author presents ahighly persuasive reading of al-Ghazali’s principal texts, which presents himas avoiding self-contradiction on this issue ...